Analysis of the Factors Influencing the Intension to Use Cross-Border QRIS as A Payment Method - Santi, Bestari Nirmala; Chalid, Dony Abdul (PT Mattawang Mediatama Solution, 2024)
Aligned with the goal of the Indonesian Payment System 2025 to accelerate inclusive finance, develop MSMEs (Micro, Small, and Medium Enterprises), streamline transactions, and enhance economic growth, the government has implemented cross-border QRIS payment system cooperation with Thailand, Malaysia, and Singapore. Technology Acceptance Model/TAM, Unified Theory of Acceptance and Use of Technology 2/UTAUT2, user system trust theories (perceived trust and perceived security), and financial literacy are integrated to identify factors influencing the intention to use cross-border QRIS. The research method is quantitative using SEM (Structural Equation Modeling), data collected through online questionnaires distributed to cross-border QRIS users. The total number of participant respondents is 356, and the data obtained are processed using SmartPLS application. The data analysis results from this study show that the intention to use QRIS cross-border is only significantly and positively affected by perceived usefulness, habit, and then hedonic motivation.